Objectively-Measured Physical Activity and Sedentary Time are Differentially Related to Dietary Fat and Carbohydrate Intake in Children - Dunton, Genevieve F.; O'Connor, Sydney G.; Belcher, Britni R.; Maher, Jaclyn P.; Schembre, Susan M. (Frontiers in Public Health, 2018)
Background: Research on the clustering of physical activity, sedentary, and dietary intake behaviors in children has relied on retrospective and parent-report measures, which may obscure true associations. The current study combined objectively-measured moderate-to-vigorous intensity physical activity (MVPA) and sedentary time (ST) data from waist-worn accelerometers, with multiple child-report 24-hour dietary recalls to assess specific components of dietary intake (i.e., dietary fat, carbohydrates, protein; glycemic load, fruits and vegetables) in children. Methods: Participants (n = 136, ages 8-12 years) wore an accelerometer for seven days. On two of those days, children completed 24-hour recall phone interviews to assess dietary intake. Results: After adjusting for child age, sex, ethnicity, annual household income, and body mass index (BMI) percentile; ST was positively associated with percent dietary fat intake, and negatively associated with percent dietary carbohydrate intake and glycemic load (p’s < .01). MVPA was positively associated with percent dietary carbohydrate intake and daily glycemic load, and negatively associated with percent dietary fat intake (p’s < .05). Conclusion: Despite its direct health benefits, physical activity may be associated with consuming greater proportion of total intake from carbohydrates, especially those with a higher glycemic index. Further research is needed to understand the differential implications of these unique behavioral interrelations for diabetes, cardiovascular, and obesity risk.